Delivering CRISPR to the HIV-1 reservoirs - Gurrola, Theodore E.; Effah, Samuel N.; Sariyer, Ilker K.; Dampier, Will; Nonnemacher, Michael R.; Wigdahl, Brian (Frontiers in Microbiology, 2024)
Human immunodeficiency virus type 1 (HIV-1) infection is well known as one of the most complex and difficult viral infections to cure. The difficulty in developing curative strategies arises in large part from the development of latent viral reservoirs (LVRs) within anatomical and cellular compartments of a host. The clustered regularly interspaced short palindromic repeats/ CRISPR-associated protein 9 (CRISPR/Cas9) system shows remarkable potential for the inactivation and/or elimination of integrated proviral DNA within host cells, however, delivery of the CRISPR/Cas9 system to infected cells is still a challenge. In this review, the main factors impacting delivery, the challenges for delivery to each of the LVRs, and the current successes for delivery to each reservoir will be discussed.